Artificial intelligence with uncertainty - Li, Deyi 1944-; Du, Yi 1971- (Chapman & Hall/CRC, 2008)
The information deluge assaulting us in the 21st century is having an impact on our lifestyles and how we work. We must separate trustworthy and required information from the massive amount of data we encounter each day. This book explores the uncertainties of knowledge and intelligence that occur during the cognitive processes of human beings